2019
DOI: 10.1002/anie.201811088
|View full text |Cite
|
Sign up to set email alerts
|

Isolable Silylene Ligands Can Boost Efficiencies and Selectivities in Metal‐Mediated Catalysis

Abstract: A significant number of isolable silylenes are currently known. They have quickly developed from laboratory curiosities to useful ligands in metal‐mediated homogeneous catalysis. This includes their utilization in various catalytic transformations, such as C−C cross‐coupling, cyclotrimerization, hydroformylation, borylation, deuteration, hydrosilylation, amination, hydrogenation, and transfer semi‐hydrogenation reactions. Recent studies suggest that the silylene ligands surpass the steering properties of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
79
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 144 publications
(81 citation statements)
references
References 97 publications
(111 reference statements)
0
79
0
2
Order By: Relevance
“…Owing to their interesting property and reactivity, stable N-heterocyclic silylenes (NHSis), the heaviera nalogues of NHCs, have been utilized successfully for the metal-free activation of small molecules [6] and as powerful steering ligandsi n homogeneous catalysis. [7] After the first isolation of an N-heter-ocyclic silylene in 1994 by Denk and West, the formation of a silylene-borane adduct was reported two years later,w hich, however,s lowly rearranges to as ilylborane through Si II insertion into the BÀCb ondo fB (C 6 F 5 ) 3 . [8] Since then, an increasing number of compounds containing ad ative Si II !B III bond with four-and five-coordinate Si II centers have been isolated and structurally characterized.…”
mentioning
confidence: 99%
“…Owing to their interesting property and reactivity, stable N-heterocyclic silylenes (NHSis), the heaviera nalogues of NHCs, have been utilized successfully for the metal-free activation of small molecules [6] and as powerful steering ligandsi n homogeneous catalysis. [7] After the first isolation of an N-heter-ocyclic silylene in 1994 by Denk and West, the formation of a silylene-borane adduct was reported two years later,w hich, however,s lowly rearranges to as ilylborane through Si II insertion into the BÀCb ondo fB (C 6 F 5 ) 3 . [8] Since then, an increasing number of compounds containing ad ative Si II !B III bond with four-and five-coordinate Si II centers have been isolated and structurally characterized.…”
mentioning
confidence: 99%
“…Silylenes are currently receiving increasing interest from the chemicalc ommunity not only because of their unique fundamental chemistry [1] but also due to their rising use as ligands in coordinationc omplexes. [2,3] Additionally,i th as been recently found that some silylenes, particularly those stabilized by donor groups,h ave as tronger electron-donor capacity than the most basic phosphanes and even N-heterocyclic carbenes (NHCs). [4,5] This is ak ey factor of their newly reported behavior as steering ligands in homogeneous catalysis, [3,4] but, despite their strong nucleophilicity, the use of silylenes as nucleophiles for the formation of SiÀCbonds is still little developed.…”
mentioning
confidence: 99%
“…[2,3] Additionally,i th as been recently found that some silylenes, particularly those stabilized by donor groups,h ave as tronger electron-donor capacity than the most basic phosphanes and even N-heterocyclic carbenes (NHCs). [4,5] This is ak ey factor of their newly reported behavior as steering ligands in homogeneous catalysis, [3,4] but, despite their strong nucleophilicity, the use of silylenes as nucleophiles for the formation of SiÀCbonds is still little developed. [1a,f,k, 6] Within the family of donor-stabilized silylenes,t hose having an amidinato fragment are being increasingly used because their syntheses are relatively easy and their electronic and steric properties can be easily tuned.…”
mentioning
confidence: 99%
“…Reported examples include complexes with coinage metals and group 6 and 8 metal carbonyls, but no further reactivity of these complexes has been reported to date. Importantly, the synthesis of new types of complexes with silicon‐based ligands and substituents is of high interest for the development of improved catalysts . With their intriguing synthetic potential, silyliumylidenes are uniquely suited for the facile synthesis of various types of Si−M (multiple) bonds (e.g.…”
Section: Introductionmentioning
confidence: 99%